Diseño de rutas turísticas que incorporen los petroglifos como mecanismo de conservación del patrimonio cultural en la parroquia San Luis de Pambil, cantón Guaranda, provincia de Bolívar” año, 2022 - Caraguay Criollo, Elda Carmen (2023)
The name of the present research work is "Design of touristic routes incorporating petroglyphs as a mechanism for the conservation of cultural heritage in the parish of San Luis de Pambil, Guaranda canton, province of Bolívar; year, 2022. Its proposal is developing touristic routes incorporating the different petroglyphs of the San Luis de Pambil parish belonging to the Guaranda canton, Bolívar province. For this, a methodological study was carried out based on an exploratory and descriptive investigation, where the current situation is described in various aspects such as the biophysical, economic, productive, population and political component in which the tourist space of the sector is located. The proposal of the touristic routes of petroglyphs and the tourist demand was made. Among the techniques used are the bibliographical research as well as the survey to determine the tourist demand of the sector. Consequently, it was observed and determined that the San Luis de Pambil parish has an interesting natural and archaeological potential for the development of its tourist activities, which is why the design of tourist routes was proposed as a measure of conservation of cultural heritage. Keywords: petroglyphs, conservation, tourism, cultural heritage, tourist routes, archaeology.